Viral interference and the live-attenuated intranasal influenza vaccine: Results from a pediatric cohort with cystic fibrosis. Issue 6 (3rd June 2017) - Boikos, Constantina; Papenburg, Jesse; Martineau, Christine; Joseph, Lawrence; Scheifele, David; Chilvers, Mark; Lands, Larry C.; De Serres, Gaston; Quach, Caroline
ABSTRACT: Background : The objective of this study was to explore the effects of viral co-detection in individuals recently vaccinated with the live-attenuated intranasal influenza virus vaccine (LAIV) on the detection of influenza RNA. Methods : Before the 2013–2014 influenza season, nasal swabs were obtained from 59 pediatric participants with cystic fibrosis (CF) and 17 of their healthy siblings immediately before vaccination and 4 times during the week of follow-up. Real-time RT-PCR assays were used to detect influenza RNA. Co-detection of a non-influenza respiratory virus (NIRV) at the time of vaccination was determined by a multiplex RT-PCR assay. Differences in the proportions and rates of influenza detection and their 95% credible intervals (CrI) were estimated. Results : Influenza RNA was detected in 16% fewer participants (95% CrI: −7, 39%) throughout follow-up in the NIRV-positive group compared with the NIRV-negative group (59% vs. 75%). This was also observed in participants with CF alone (66% vs. 74%; RD = 8% 95% CrI: −16, 33%) as well as in healthy participants only (75% vs. 30%; RD = 45%, 95% CrI: −2, 81%). Influenza was detected in NIRV-negative subjects for 0.49 d more compared with NIRV-positive subjects (95% CrI: −0.37, 1.26). Conclusion : The observed proportion of subjects in whom influenza RNA was detected and the duration of detection differed slightly between NIRV- positive and −negative subjects. However, wide credible intervals for the difference preclude definitive conclusions. If true, this observed association may be related to a recent viral respiratory infection, a phenomenon known as viral interference.